IMPLEMENTASI PERKAWINAN SEDARAH PADA MASYARAKAT DESA SEROMBOU INDAH KECAMATAN RAMBAH HILIR KABUPATEN ROKAN HULU - Suryani '; Hayatul Ismi; Maryati Bachtiar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Marriage is one of the most important events in human life. Indonesian people who still hold firm customs also know the term